Changes in sources and income levels in Samata Village, Somba Opu District, Gowa Regency. Issue 1 (March 2021) - Akhsan,; Sarah, A; Fahmid, I M; Diansari, P; Ali, M S S; Mahyuddin,; Sukardi, L
Abstract: Shifting people's livelihoods is the change of a population's work from agriculture to non-agriculture, which is a source of income to finance the living needs of each family. This study aims to determine changes in sources and income levels in Samata Village, Somba Opu District, Gowa Regency. The data analysis technique used is a descriptive qualitative analysis using frequency tables. The results of this study indicate that the change in source and income level in the Samata village is marked by the transfer of livelihood sources, which results in a change in the amount of income.